The Newcastle Pediatric Mitochondrial Disease Scale: translation and cultural adaptation for use in Brazil - Gabriela Palhares Campolina-Sampaio; Laura Maria de Lima Belizário Facury Lasmar; Beatriz Silva Vilela Ribeiro; Juliana Gurgel Giannetti (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective The aim of this study was to translate and adapt the Newcastle Paediatric Mitochondrial Disease Scale (NPMDS) to Portuguese for use in Brazil. Methods The scale was applied in 20 pediatric patients with mitochondrial disease, in three groups: myopathy (n = 4); Leigh syndrome (n = 8); and encephalomyopathy (n = 8). Scores were obtained for the various dimensions of the NPMDS, and comparisons were drawn between the groups. Results There was a statistically significant difference between the myopathy group and the Leigh syndrome group (p = 0.0085), as well as between the myopathy and encephalomyopathy groups (p = 0.01). Conclusions The translation of the NPMDS, and its adaptation to the socioeconomic and cultural conditions in Brazil, make the NPMDS score useful as an additional parameter in the evaluation and monitoring of pediatric patients with MD in Brazil.